Death education in Malaysia: from challenges to implementation / Hui Zanne Seng and Phei Wei Lee - Hui, Zanne Seng; Phei, Wei Lee (Universiti Teknologi MARA, Pulau Pinang, 2022)
The paper aims to provide a glimpse of the importance of death education, proposed strategies to be implemented and proposed model for death education programs in the Malaysian context, taking note of the new norm during the pandemic. By reviewing the literature and the trend of death education nationwide, the paper attempts to respond to the current trend of death education and what should be included to increase its efficacy in the local Malaysian context. It was found that there are some challenges in implementing death education, mainly due to the stigma, limited resources, willingness of the participants to sign up and participate, and the lack of a more comprehensive series of death education that will solidify the learnings and increase the efficacy of death education in Malaysia. In conclusion, to enhance the benefit of death education, it is encouraged to implement it in a sequential series encompassing theoretical, experiential and reflective components, consisting of religion and spiritual wisdom, immersive activities, and a participant-and-trainer engagement friendly medium, to provide a more holistic experience to encourage for a more positive attitude towards death education and conversations.